Bases filosóficas e implicações técnicas na Gestalt-terapia - Porto, Rosane Carneiro (1989)
The objective of this work is an epistemological reflection on Gestalt-therapy philosophícal basis, trying to associate it with its techniques and therapeutic procedures. Gestalt-therapy is shown from its origin, including a biography of Fritz Perls, where the influence of other approaches in his mind is evinced. The philosophic presuppositions are highlighted trying to relate some central concepts of phenomology and existencialism with Gestalt-therapy. A brief introduction on the basic theoretical pressuppositions was inserted, to help a better understanding of the approach as a whole. The therapeutic attitude is investigated supported on man's vision revealed in the philosophic essentials. It finishes whith some critical considerations on Gestalt-therapy. This analysis leads to the following inferences which refer to the therapeutic line focused. Philosophically it is based on man's existencialist vision which appraised existence, subjectivity and singularity, letting pain, anguish and suffering emerge. It ascertains that there is no human nature. Man is an interrelational being and his innermost essence is mistery. Human being only reveals himself in freedom; he is responsible for his choices. The therapeutic attitude adopted is phenomenologic¬ existential. The therapeutic situation phenomena are seen free from any 'a priori'. The therapist keeps up with the client's conscience flow trying to understand what is being unveiled to him and enthrall its meaning.